Mechanical and thermal properties of wood fiber reinforced geopolymer composites. Issue 13 (1st December 2022) - Furtos, Gabriel; Molnar, Luminita; Silaghi-Dumitrescu, Laura; Pascuta, Petru; Korniejenko, Kinga
ABSTRACT: Geopolymers based on fly ash are an emerging alternative to ordinary Portland cement, with a low impact on the environment and a potential to increase the sustainability of the concrete-based construction. Reported here is the design and investigation of new wood fiber reinforced geopolymer composites (WFRGC) based on fly ash and wood fiber (5–35 wt%). These WFRGC showed reduced mechanical properties with rising wood fiber addition as calculated by compressive strength with the cylindrical test (7.83–59.82 MPa); compressive strength at cubic test (6.95–50.23 MPa); force load at upper yield (0.70–5.02 KN); flexural strength (1.71–11.05 MPa); compressive modulus at cubic test (0.13–054 GPa); and flexural modulus (3.91–1293.61 MPa). The adding of wood fiber showed decreases of the density WFRGC (1.58–1.87 g/cm 3 ) and decreases the thermal conductivity of WFRGC. The addition 20 wt% wood fiber could be the limit for acceptable mechanical properties. WFRGC with 20–35 wt% wood fibers may be a promising green material for building.